Homicides due to positional asphyxia: Two case reports (2014)
Homicides by positional asphyxia do not come up very often within forensic literature in contrast to other ways of asphyxia have been frequently described. This article describes two cases in which the autopsy findings of the external and internal examination, may suggest patterns for future studies and/or reference points for studying this kind of death. In addition, it could open discussion about an unfrequented topic in forensics.The analysis of this case report aims to understand positional asphyxia as a homicide method in order to shed light on such a complex and rare kind of death. © 2014 Romanian Society of Legal Medicine.